The bladder cancer patient survey: Global perspectives on awareness and treatment of bladder cancer. (December 2019) - Elliott, Josephine; Rotterud, Ranveig; Maddox-Smith, Andrea; Bagshaw, Ken; Cirefice, Lori Beth Funk; Knight, Allen; Necchi, Andrea; Rek, Anna; Winterbottom, Andrew; Makaroff, Lydia Elizabeth
Graphical abstract: Highlights: The most common initial bladder cancer symptom was visible blood in the urine. Bladder cancer was not the first diagnosed condition in ¾ patients. Half of the respondents had a parent or sibling diagnosed with cancer. Awareness of bladder cancer differed between countries. Support systems included friends/family, and online and patient advocacy groups. Abstract: Introduction: Bladder cancer is the ninth most common cancer globally, but, to date, few studies have examined the personal experience of bladder cancer patients. This study examines three key areas in bladder cancer patient experience: diagnosis, treatment, and support. Method: An online, multiple-choice questionnaire was designed to collect data regarding bladder cancer patient experience. The study was created, translated, and disseminated electronically via email and social media by the European Cancer Patient Coalition and national bladder cancer organisations and groups. The web-based online survey was conducted between September 2017 and April 2018. Results: The survey yielded responses from 1615 participants originating from 39 countries. The most common initially reported symptom of bladder cancer was visible blood in the urine (72.8 % of respondents). Three-quarters (74.7 %) of respondents reported that their initial diagnosis was a condition other than bladder cancer. The most popular form of support reported for coping with bladder cancer, for both patients and carers, was friends and family (69.7 %), followed by online support groups (58.3 %). Country comparison showed that awareness of bladder cancer differed widely between countries. Conclusions: There is a need for greater awareness and understanding of bladder cancer. Further research is warranted to promote early diagnosis and the timely treatment of bladder cancer.